دراسة تأثير الخواص الوراثية للصنف في حجم ونوعية درنات خمسة أصناف بطاطا مدخلة حديثاً إلى سورية - شيخ سليمان, نصر; عثمان, جنان (Latakia University Journal -Biological Sciences Series, 2014)
تضمن البحث دراسة تأثير خواص الصنف الوراثية في حجم الدرنات وتركيبها الكيميائي لخمسة أصناف بطاطا مدخلة حديثاً الى القطر( أطلس Atlas ، بورين Bureen ، بومبا Bomba ، رومبا Rumba، والصنف أورلا Orla) إضافة إلى الشاهد سبونتا Spunta، نفذ البحث في مشتل جامعة تشرين في عروة ربيعية للموسم الزراعي 2012 . أظهرت النتائج أن الأصناف أطلس، وبورين، وبومبا أعطت أكبر نسبة من الدرنات الكبيرة الحجم، في حين سجل الصنف بومبا أعلى إنتاجية للدرنات التسويقية (7.8 كغ/م2). كما أظهرت النتائج أن أعلى نسبة للمادة الجافة ( 20.5%) والرماد (1.01%) سجلت في الصنف رومبا، بينما أعلى نسبة للنشا سجلت في الصنفين سبونتا وبورين ( 14.5 و 14.4 % )على التوالي، وسجلت الأصناف رومبا وسبونتا وبورين أعلى نسبة لفيتامين C ( 19.36 ، 17.6، 17.6 مغ / 100 غ ) على التوالي، وتميز الصنف رومبا بأكبر نسبة للبروتين (1%) والمواد الصلبة الذائبة الكلية (5%). This research work was carried out in the nursery field of the Faculty of AGgriculture in Tishreen Univesity during the spring growing season of 2012, it involved studying some chemical characteristics of potato tubers of Five newly introduced varieties of potato ( Atlas, Bureen, Bomba, Rumba and Orla), in comparision with Spunta variety as a control. It was showed that the hieghest large tuber were recorded in Atlas ,Burren and Bomba. Bomba variety showed hieghest standards tubers (7.8 Kg/ m2). It was showed also the hieghest dry matter (DM=20.5 %), and Ash content (1.01%) in tubers, were recorded in Rumba variety. Bureen and Spunta varieties showed hieghest values of starch contents (14.5 % and 14.4%) respectively. While Vitamin C (VC ( , was encountered ( 19.36, 17.6, and 17.6 mg / 100g) for Rumba, Spunta and Bureen respectively. Also, the highest values for protein content (1%) and the soluble solid (5%) in tubers were found in Rumba variety.